2018
DOI: 10.1016/j.chembiol.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

The Advantages of Targeted Protein Degradation Over Inhibition: An RTK Case Study

Abstract: Proteolysis targeting chimera (PROTAC) technology has emerged over the last two decades as a powerful tool for targeted degradation of endogenous proteins. Herein we describe the development of PROTACs for receptor tyrosine kinases, a protein family yet to be targeted for induced protein degradation. The use of VHL-recruiting PROTACs against this protein family reveals several advantages of degradation over inhibition alone: direct comparisons of fully functional, target-degrading PROTACs with target-inhibitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
479
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 480 publications
(522 citation statements)
references
References 63 publications
13
479
0
1
Order By: Relevance
“…They showed that the PROTACs significantly decreased cellular levels of ALK fusion proteins in different cell lines including SU-DHL-1 (lymphoma) and NCI-H2228 (lung cancer). 94 Interestingly, the PROTAC mediated the internalization of EGFR and sorted to lysosomal degradation, 94 although the RTKs usually prefer to internalize into a recycle endosome. 80 Kang et al later on proved that a synthesized PROTACs against ALK (based on VHL) worked in vivo.…”
Section: Targeting Protein Kinasesmentioning
confidence: 99%
“…They showed that the PROTACs significantly decreased cellular levels of ALK fusion proteins in different cell lines including SU-DHL-1 (lymphoma) and NCI-H2228 (lung cancer). 94 Interestingly, the PROTAC mediated the internalization of EGFR and sorted to lysosomal degradation, 94 although the RTKs usually prefer to internalize into a recycle endosome. 80 Kang et al later on proved that a synthesized PROTACs against ALK (based on VHL) worked in vivo.…”
Section: Targeting Protein Kinasesmentioning
confidence: 99%
“…Compound 3i can completely knockdown TBK1 in several cancer cell lines at a concentration of 100 nM, indicating the excellent efficiency of this compound (Figure d) . In addition, VHL‐based PROCTACs have been shown to target transmembrane receptor tyrosine kinases (RTKs) as well as mutants of RTKs …”
Section: All‐small‐molecule Protacs: a Potent And Promising Tool To Ementioning
confidence: 95%
“…Targeted protein degradation, using heterobifunctional small molecules (PROTACs) to remove protein targets from within cells, has emerged as a novel strategy for drug development, with the opportunity of providing therapeutic interventions not achievable with existing occupancy‐based enzyme inhibition approaches . Small‐molecular‐weight synthetic PROTACs ( 185‐189 ) have been used to selectively degrade various specific proteins (Figure ), including pirin, sirt2, BET protein, androgen receptor, and BRD4 protein …”
Section: Exploitation Of Solvent‐exposed Regions For the Rational Desmentioning
confidence: 99%
“…into one molecule, to take advantage of the presence of large hydrophobic patches at the HDAC surface rim. 122 Some encouraging results have been reported (Figure 22), such as dual-acting HDAC and topoisomerase II inhibitor On the basis of these analyses, a structure-based hybridization strategy was used to discover novel Mcl-1/Bcl-xL dual inhibitors (159,160) with a suitable linker based on 157 and 158 ( Figure 22). Notably, compound 160 displayed the potent dual-inhibitory activities (Mcl-1, IC 50 = 0.088 μM; and Bcl-xL, IC 50 = 0.0037 μM) ( Figure 23).…”
Section: Many Of These Inhibitors Show Potency Against Rt and In At Mmentioning
confidence: 99%